Kombinasi Pupuk Anorganik dan Pupuk Organik Meningkatkan Produksi Tanaman Tomat (Licopersicum esculentum Mill) dengan Pemangkasan Pucuk Apikal: Combination of Inorganic and Organic Fertilizer on The Production of Tomato (Licopersicum esculentum Mill) with Appical Uper Pruning - Maria Klara Salli; Yosefina Lewar; Mahmudah Hamawi (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2024)
The research aims to determine the effect of a combination of inorganic fertilizer (KNO3) and organic fertilizer (goat manure) on the yield of the Betavila variety when apical shoots are pruned. The research took place from March to October 2019 in Kupang Regency, NTT. The research used RAK with 4 repetitions. The treatments are as follows: M1 = inorganic fertilizer 5 g/l KNO3; M2 = organic fertilizer 20 tons/ha goat manure; M3 = inorganic fertilizer 5 g/l KNO3 + organic fertilizer 30 tons/ha goat manure; M4 = inorganic fertilizer 5 g/l KNO3 + organic fertilizer 15 tons/ha goat manure; M5 = Inorganic fertilizer 3.75 g/l KNO3 + organic fertilizer 15 tons/ha goat manure; M6 = Inorganic fertilizer 3.75 g/l KNO3 + organic fertilizer 30 tons/ha goat manure; M7 = inorganic fertilizer 2.5 g/l KNO3 + organic fertilizer 15 tons/ha goat manure; M8 = inorganic fertilizer 2.5 g/l KNO3 + organic fertilizer 30 tons/ha goat manure. The results of the research showed that the combination of applying inorganic fertilizer and organic fertilizer simultaneously influenced the yield of Betavila variety tomato plants whose apical shoots had been pruned, namely on the number of fruits, fruit weight, and fruit production. Fertilization dose of inorganic fertilizer 3.75 g/l KN03 + organic fertilizer 30 tons/ha goat manure gave the number of fruits per plant (59.63 fruit), fruit production per plant (2.63 kg), and fruit production per experimental plot (50.33 kg) highest.